A Systematic Review on The Role of Artificial Intelligence in Assisted Reproductive Technology - Latika; Dr. Renuka Arora (International Journal of Bioinformatics and Computational Biology, 2026)
Artificial Intelligence (AI) has significantly transformed Assisted Reproductive Technology (ART) over the past five years, enhancing diagnostic accuracy, treatment personalization, and overall success rates. AI-driven algorithms and machine learning models have been integrated into various aspects of ART, including sperm selection, embryo grading, and predicting implantation success. Deep learning techniques have improved image-based embryo assessment, reduced human subjectivity and increased efficiency. Additionally, AI-powered predictive analytics have helped optimize ovarian stimulation protocols and identify potential causes of infertility. AI has proved its worth in all most all sectors, it has the potential to bring a boom in Reproductive field as well as AI can help to analyze the data and can predict results which may help the women who wish to conceive through ART techniques. This will improve overall health, mental condition and create an understanding between patient and doctor, which will result increase in success rate of pregnancy achieved through ART methods. This review highlights the role of Artificial Intelligence in ART like IUI, IVF and ICSI, discusses its impact on clinical outcomes, and explores future possibilities in the field. Paper aims to focus on role of AI in ART techniques, AI in ART in low- and middle-class families, embryo selection using AI, sperm selection using AI. Paper also gives a review of factors for the success of ART through AI with focus on providing personalized experience through AI to the women patients. Along with this role of AI in ICSI and IUI is also reviewed. While AI has shown great promise in improving reproductive success, ethical considerations and regulatory frameworks remain crucial to ensure safe and effective implementation in clinical practice.
Keywords: AI; Art; FET; ICSI; IUI; IVF; ML; Robotics; embryos